Business strategies and competitive advantage factors in the electronics industry in Malaysia - Md Zabid Abdul Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2000)
This paper examines the relationship between business (generic) strategies and the competitive advantage factors of firms in the electronics industry. The paper also investigates the extent of influence of generic strategies on the competitive advantage factors. A structured questionnaire was developed and administered to the chief executive officers (CEO) of the firms in the electronics industry in Malaysia. Based on 85 useable responses, the data were analysed using factor analysis (principal component solution), and subsequently the K-Means cluster analysis. The findings of the study showed that there is a positive relationship between each of the generic strategies and the competitive advantage factors. This implies that firms had a variety of sources in order to gain or sustain their competitive advantage positions in the industry. The results of MANOVA indicate the extent of influence of the generic strategies and competitive advantage factors. The implications of the findings are also discussed